DINAMIKA PLATFORM INVESTASI BAREKSA DAN MOTION TRADE: ANALISIS DEKSRIPTIF - Nurul Azizah; Wahyu Fahrul Ridho (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
Indonesian investors increased by 260 thousand people from January 2022. The increase was dominated by the millennial generation and generation Z who are active in the digital world. Investment type growth data from KSEI (2021) shows that investment types are dominated by the capital market and mutual funds by 16.35% and 20.50% in February 2021. Various investment platforms that are currently emerging offer multiple features ranging from investing in stocks, mutual funds, gold, and crypto. Ease of access to digital investment platforms is one of the factors that play a role in investor growth. It is essential to provide a safe and easy-to-learn platform for investors to gain confidence in this context, along with wider access to investment. Investment applications can be analyzed from the perspective of TAM theory, namely, the process of facilitating and using an investment application. This study used a descriptive method based on TAM theory which analyzes the Bareksa investment platform and MotionTrade. The results of this study showed that the Bareksa platform and MotionTrade have the same level of trust from users, while the user risk acceptance variable assesses that the Bareksa platform has a greater risk than the MotionTrade platform. In the following variable, perceived usefulness, the result showed that the Bareksa platform was higher than the MotionTrade platform. Variable perceived ease of use on the MotionTrade platform was easier than the Bareksa platform. Investor Indonesia meningkat sebesar 260 ribu orang per januari 2022. Kenaikan tersebut didominasi generasi millennial dan generasi Z yang aktif dalam dunia digital. Data pertumbuhan jenis investasi dari KSEI (2021) jenis investasi didominasi pada pasar modal dan reksadana sebesar 16,35% dan 20,50% pada februari 2021. Berbagai platform investasi yang muncul saat ini menawarkan beragam fitur mulai dari investasi saham, danareksa, emas dan crypto. Kemudahan akses terhadap platform investasi digital menjadi salah satu faktor yang berperan terhadap pertumbuhan investor. Namun semakin meluasnya akses terhadap investasi harus diiringi dengan literasi keuangan dan platform yang aman dan mudah dipelajari untuk meningkatkan kepercayaan pengguna dalam konteks ini investor. Penggunaan aplikasi investasi oleh investor dapat di analisis dari teori TAM yaitu, proses kemudahan dan kegunaan sebuah investasi. Pada penelitian ini menggunakan metode deskriptif yang berdasar teori TAM yang menganalisis platform investasi bareksa dan motion trade. Hasil penelitian ini menunjukkan bahwa platform bareksa dan motion trade memiliki tingkat kepercayaan yang sama dari pengguna, sedangkan pada variabel penerimaan resiko pengguna menilai platform bareksa memiliki resiko lebih besar dibandingkan platform motion trade. Pada varibel berikutnya perceived of usefulness diperoleh hasil bahwa platform bareksa lebih tinggi dibandingkan platform motion trade. Variabel perceived ease of use pada platform motion trade lebih mudah dibandingkan platform bareksa.